Guerilla warfare - Weir. ([S.l.] : Motilal UK Books of India, 2009)
The twentieth century produced scores of such conflicts, whether as sideshows of the world wars or as the main events in wars of revolution or liberation. "Guerrilla Warfare" examines twenty-one of these conflicts, shedding light on the remarkable capabilities of unconventional fighters to outlast and defeat their enemies. "Guerrilla Warfare" covers a century of unconventional fighters at war including: succinct accounts of 21 guerrilla conflicts in the twentieth century; the exploits of men like Lawrence of Arabia, Orde Wingate, Mao Zedong, and Che Guevera; the American hunt for Pancho Villa; Mao versus Chiang in the Chinese Civil War; the showdown at Dien Bien Phu in 1954; France's long war in Algeria; the Siege of Khe Sanh in the Vietnam War; the Afgan-Soviet War from 1979 to 1989; and, more.